Detection of Coronavirus Strain 692 by Immune Electron Microscopy - Kapikian, Albert Z. (1973)
Utilization of the technique of immune electron microscopy has enabled the detection of a coronavirus in organ culture harvests derived from a washing from an adult with an acute upper respiratory tract illness; convalescent serum was the source of specific antibody.